Development of a Problem-Based Learning Interactive E-Module to Improve Learning Outcomes in Lathe Machining Techniques at Vocational High School - Theo Radhitya; Anis Rahmawati; Budi Tri Cahyono (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
This study aims to develop and evaluate the effectiveness of an interactive e-module based on Problem-Based Learning (PBL) to improve students' cognitive learning outcomes in lathe machining techniques. The research was conducted using the Research and Development (R&D) method with the Alessi and Trollip development model, involving stages of planning, design, and development. The resulting e-module was created using Flip PDF Professional and enriched with multimedia elements such as animated explanations, instructional videos, and quizzes. The media was validated by experts and tested on 64 students from a vocational school in Magetan, Indonesia. Statistical tests including the Kolmogorov-Smirnov test, Levene’s test, paired sample t-test, and N-Gain analysis were applied to evaluate the normality, homogeneity, significance, and effectiveness of the learning outcomes. The results showed that the PBL-based e-module significantly improved students' learning performance, with an average N-Gain score of 0.71 (high category). Furthermore, student response was overwhelmingly positive, with a satisfaction rate of 93.13%. The integration of PBL within an interactive digital platform successfully increased student engagement, supported higher-order thinking, and fostered deeper conceptual understanding. These findings confirm that interactive e-modules designed with PBL can serve as effective instructional tools in vocational education settings.